Functional and union outcome of combined column tibial plateau fracture treated with hybrid external fixator - Anis, Muhammad; Gillani, Syed Faraz Ul Hassan Shah; Mohy-Ud-Din, Iftikhar (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the combined column tibial plateau fracture treated with a hybrid external fixator in terms of knee functionality, union outcome and complications. Method: The quasi-experimental study was conducted at the Department of Orthopaedic Surgery, Mayo Hospital, Lahore, Pakistan, from July 5, 2019, to December 31, 2021, and comprised patients of either gender aged 20-50 years who presented with 2-column or 3-column fractures of proximal tibia classified according to the 3-column classification system after being diagnosed using radiographs and three-dimensional computed tomography scan. Knee function, union and complications, like neural, vascular, infection, delayed union, nonunion, malunion and implant failure, were evaluated. The Knee Society Score was used to assess knee function, and modified Rasmussen score for the union, while complications were assessed clinically on the 2nd, 6th, 12th, 16th, 24th, 36th weeks and one year post-operatively. Data was analysed using SPSS 26. Results: Of the 113 patients, 91(80.53%) were males and 22(19.47%) were females. The overall mean age was 35.56±9.00 years. From the 12th week to the 24th week 45(39.83%) patients had good and 59(52.21%) patients had excellent functional outcomes. Union outcome in the 16th and 24th week was good in 57(50.44%) patients and excellent in 47(41.59%) patients. No neurovascular injury was observed. Superficial pin tract infection was observed in 21(18.6%) cases that healed with wound debridement and antibiotics. No delayed union, malunion and implant failure was observed. Conclusion: Good to excellent functional and union outcomes with minimum complications were observed with the hybrid external fixator. Key Words: Tibial plateau fracture, Knee joint, Hybrid external fixator, Union, Combined column.